1997
DOI: 10.1002/(sici)1097-4660(199706)69:2<276::aid-jctb711>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Temperatures on the Performance of an Anaerobic Baffled Reactor (ABR)

Abstract: The effect of a decrease in operating temperature on the performance of two 10 dm3 anaerobic baffled reactors (ABR) was examined in terms of steady state chemical oxygen demand (COD) removal efficiency. To minimise variations, and have a totally biodegradable feed, a synthetic carbohydrate (sucrose)–protein (meat extract) substrate was used. The reactors were operated at 20 h hydraulic retention time (HRT), 4 g dm−3 COD, and 35°C as a base‐line condition. Because of their different histories, the reactors resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Biogas production is affected by pretreatment methods used for dung and straw and by temperature, the ratio of carbon to nitrogen, and trace elements. [19] Furthermore, it has been shown that trace elements are also essential nutrients for micro-organism activity [20,21] and for the structure of enzymes, such as methyl-coenzyme M reductase and the coenzyme M methyltransferase complex.…”
Section: Introductionmentioning
confidence: 99%
“…Biogas production is affected by pretreatment methods used for dung and straw and by temperature, the ratio of carbon to nitrogen, and trace elements. [19] Furthermore, it has been shown that trace elements are also essential nutrients for micro-organism activity [20,21] and for the structure of enzymes, such as methyl-coenzyme M reductase and the coenzyme M methyltransferase complex.…”
Section: Introductionmentioning
confidence: 99%
“…This greater removal suggests the process was not fully loaded. First stage bioreactors for carbon removal might be expected to operate at >1kgBOD/m 3 .day but better performance at higher organic loadings are reported in this study compared to some previous other work on high levels of performance, for example Masse and Massé [8] and Nachaiyasit [4]. This was attributed to higher biomass concentrations and better mixing.…”
Section: Toc Removalmentioning
confidence: 45%
“…Masse and Massé [8] reported on larger organic shock loads (OLR was increased from 2.60 TCODg/L/day to 3.92 TCODg/L/day with a maximum 6.25 TCODg/L/day) to four SBRs and also reported a small and temporary effect on performance efficiency measured as Soluble Chemical Oxygen Demand (SCOD) and Volatile Fatty Acid (VFA) concentrations. Although Nachaiyasit [4] believed that during hydraulic shocks the rate of mass transfer of substrate into the biomass aggregates appeared to be the limiting factor. The major factor controlling the overall performance rate during organic shocks should be the kinetics of the uptake and consumption by the biomass.…”
Section: Toc Removalmentioning
confidence: 99%
See 2 more Smart Citations